Exploring EFL Fluency in Asia
XXII, 331 p.
Keywords: In EFL contexts, an absence of chances to develop fluency in the language classroom can lead to marked limitations in English proficiency. This volume explores fluency development from a number of different perspectives, investigating measurements and classroom strategies for promoting its development.